Self-reports from behind the scenes: Questionable research practices and rates of replication in ego depletion research. - Wanja Wolff; Lorena Baumann; Chris Englert (PLoS ONE)
The strength model of self-control is one of the most influential and well-established models of self-regulation in social psychology. However, recent attempts to replicate the ego depletion effect have sometimes failed. The goal of this study is to investigate self-reported replication rates and the frequency of a set of questionable research practices (QRP) in ego depletion research. A literature search resulted in 1721 researchers who had previously published on ego depletion. They were invited to participate in an anonymous online survey. The respondents (n = 277), on average, had published over three papers on ego depletion, and had completed more than two additional, unpublished studies. Respondents indicated that in more than 40% of their studies, results were similar in magnitude to those reported in the existing literature, and more than 60% reported conducting a priori power analyses. 39.2% of respondents were aware of other researchers who engaged in the surveyed QRP's, while 37.7% affirmed to have employed said QRP's. These results underline the importance of reducing QRP's to reliably test the validity of the ego depletion effect.